2010
DOI: 10.3109/08860221003675260
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors leading to reduced bone mineral density in hemodialysis patients with metabolic syndrome

Abstract: Although metabolic syndrome (MS) is associated with low bone mineral density (BMD) in the general population, it is unknown whether similar associations exist in patients with chronic kidney disease. We investigated risk factors that can lead to low BMD values in hemodialysis patients with MS according to the diagnostic criteria set by International Diabetes Federation (IDF) in this study. A total of 64 patients with MS undergoing hemodialysis and 60 hemodialysis patients who were matched in terms of age, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
9
0
2
Order By: Relevance
“…Calcium levels positively correlated with BMD at all measured sites. Several studies in CKD patients have not previously reported this association 25,[38][39][40] . It should be noted that calcium levels in our study were measured only during the three months before the determination of BMD and therefore do not reflect the long-term impact of calcium levels on BMD.…”
Section: Both Gender Females Malesmentioning
confidence: 90%
See 1 more Smart Citation
“…Calcium levels positively correlated with BMD at all measured sites. Several studies in CKD patients have not previously reported this association 25,[38][39][40] . It should be noted that calcium levels in our study were measured only during the three months before the determination of BMD and therefore do not reflect the long-term impact of calcium levels on BMD.…”
Section: Both Gender Females Malesmentioning
confidence: 90%
“…Several studies of dialysis patients have reported the same findings [21][22][23][24] . On the other hand, some other stud- [25][26][27] ). In our study, no statistically significant differences were found either in BMD values (expressed as g/cm 2 and T-score) or in the prevalence of T-scores ≤ -2.5 SD between non-diabetic and diabetic patients.…”
Section: Both Gender Females Malesmentioning
confidence: 99%
“…95 Binici and Gunes 96 found no association between heparin use and reduced bone mineral density in hemodialysis patients with metabolic syndrome. Lai et al 97 found that bone mineral density was lower in a cohort of 40 stable hemodialysis patients treated with heparin than in age-matched controls without either kidney disease or heparin use, but this was confounded because bone mineral metabolism is deranged in all patients with kidney failure.…”
Section: Complications Of Ufh Usementioning
confidence: 97%
“…Increasing age, diabetes, smoking, glucocorticoid therapy, and mineral metabolism have been described as risk factors for bone loss (19,20). The prevalence of CAC is also elevated among nondialyzed CKD patients and it has been associated with future cardiovascular events, hospitalization, and mortality (12).…”
Section: Discussionmentioning
confidence: 99%